Analisis Dampak Krisis Moral pada Siswa Sekolah Dasar Era Revolusi Society 5.0 - Zalianti, Gusmita; Sari, Maya; Gusmaneli, Gusmaneli (Indonesian Journal Publisher, 2024)
A crisis is an event that has more negative implications in an organization. The crisis also has much potential for the negative in affecting an organization or a company and in the community. Whereas morals are things that fit with ideas which are commonly accepted by humans, which are good and which are bad. Assessments of morals are measured in local cultures. When such a person does according to the values that are in society it is accepted and the person has good value. So the moral crisis is the negative that can influence a system and aspects of that good life in the home, school, and community environment. The crisis phase is that crisis build up, the second crisis breakout, the third chrinic crisis stage, and the last crisis stage. Furthermore, the revolutionary society 5.0 concept, which will play a major role in transforming data into a new kind of wisdom that ultimately enhances human ability, opens the door to a meaningful life. In the society 5.0 era a great amount of information would accumulate in the virtual world. The impact is that the world is becoming so connected that national boundaries seem to be lost.